2014
DOI: 10.4103/1673-5374.137593
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude of sensory nerve action potential in early stage diabetic peripheral neuropathy: an analysis of 500 cases

Abstract: Early diagnosis of diabetic peripheral neuropathy is important for the successful treatment of diabetes mellitus. In the present study, we recruited 500 diabetic patients from the Fourth Affiliated Hospital of Kunming Medical University in China from June 2008 to September 2013: 221 cases showed symptoms of peripheral neuropathy (symptomatic group) and 279 cases had no symptoms of peripheral impairment (asymptomatic group). One hundred healthy control subjects were also recruited. Nerve conduction studies reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 0 publications
3
17
0
Order By: Relevance
“…Similarly, in a recent study [8] on a larger sample of 500 patients affected by diabetic neuropathies at an early stage, the SNAP amplitude turned out to be the most sensitive neuropathy marker, in agreement with previous findings by Bi et al [9]. The highest rate of abnormality was observed in the median nerve SNAP (42.3%), followed by alterations in that of the ulnar (36.6%) [8].…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Similarly, in a recent study [8] on a larger sample of 500 patients affected by diabetic neuropathies at an early stage, the SNAP amplitude turned out to be the most sensitive neuropathy marker, in agreement with previous findings by Bi et al [9]. The highest rate of abnormality was observed in the median nerve SNAP (42.3%), followed by alterations in that of the ulnar (36.6%) [8].…”
supporting
confidence: 90%
“…Although we are aware that such an opinion about the particular usefulness of upper limb nerve conduction studies in DM is currently supported by limited evidence [3,4,7,8], we do feel that this is something that should be taken into account carefully when the nerve conduction criteria for diagnosis of diabetic neuropathies is being assessed''. As the aforementioned criterion of 1 abnormal attributes in 2 nerves has been reported to be the most useful to obtain a good sensitivity and specificity [2], we propose that the median and ulnar nerve, in their motor and sensitive component, be the two target nerves for an early diagnosis of diabetic neuropathies.…”
mentioning
confidence: 96%
“…Confirming Zhang et al [46] and Zhong et al [38], Rota et al [47] report NCV changes typical of entrapment neuropathy to be present in 70% of a consecutive series of patients referred to an Italian diabetology unit.…”
Section: Objective Outcomesmentioning
confidence: 53%
“…However, the heterogeneity of the method for evaluating DN may be the primary barrier to clarify the effect of glycemic control on DN progression ( 14 ). In patients with DN, nerve conduction studies revealed abnormalities, such as reduced amplitude, slowed conductive velocity, or prolonged latent phase ( 23 ). Distal, symmetrical, length-dependent sensorimotor polyneuropathy, which is the most common pattern of DN, is associated with progressive distal axonopathy ( 24 ).…”
Section: Discussionmentioning
confidence: 99%